PERSEPSI ORANG TUA, GURU DAN TENAGA KESEHATAN TENTANG OBESITAS PADA ANAK DAN REMAJA - Sumarni, Sumarni; Bangkele, Elli Yane (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2023)
Obesity is a problem in many parts of the world with a rapidly increasing prevalence. The prevalence of obesity in children and adolescents also occurs in Central Sulawesi Province. This study aims to determine the perceptions of parents, teachers, and health workers on obesity in children and adolescents. This study uses a qualitative method with a cross-sectional approach. Determination of respondents using purposive sampling with objective criteria of having an obese nuclear family, obese students, and health workers associated with the nutrition program. The total number of respondents is 22 people. Data collection through interviews using a questionnaire containing 6 open questions. The results of the study generally provide an overview of people's perceptions of obesity, obesity in adolescents, the impact of obesity on the health and daily activities of adolescents, as well as the prevention of obesity in children and adolescents. In general, people have understood the meaning, health impact, and prevention of obesity in children and adolescents. However, there is still an opinion that considers obesity in children and adolescents as something that makes the family proud